Wildlife diversity of Malagufuk Forest, Papua for sustainable ecotourism and community-based forest management - YOSEP RUSLIM; Amatus Turot; Chandra Dewana Boer; Paulus Matius; Jonni Marwa; Rujehan Rujehan; Rustam Rustam; Rachmat Budiwijaya Suba; Ali Suhardiman; Rochadi Kristiningrum (Society for Indonesian Biodiversity, 2025)
Malagufuk Forest in Southwest Papua is a biodiversity hotspot with significant ecological and economic potential for ecotourism and community-based forest management. This study aims to assess the diversity of birds, mammals, amphibians, and reptiles in the region and explore their implications for conservation and sustainable tourism. The research employed a combination of direct and indirect observation methods, including mist nets, camera traps, and community interviews. A total of 29 bird species from 14 families, seven mammal species from six families, and nine amphibian and reptile species were identified. Several species, including the iconic Birds-of-Paradise and cassowaries, are protected under Indonesian and international conservation regulations. The findings highlight the importance of maintaining forest cover for species richness and ecosystem stability. However, challenges such as habitat disturbance and unsustainable land use pose threats to biodiversity conservation. The study suggests that integrating conservation strategies with ecotourism development can provide economic benefits to local communities while ensuring wildlife protection. Sustainable management, community engagement, and infrastructure development are key to preserving Malagufuk's ecological integrity and promoting responsible tourism. This research supports the establishment of Malagufuk as a model for ecotourism-based conservation in Papua